Modeling of a Novel Atmospheric SOFC/GT Hybrid Process and Comparison with State‐of‐the‐Art SOFC System Concepts. Issue 5 (23rd September 2020) - Cardenas De La Cruz, C. T.; Herz, G.; Reichelt, E.; Jahn, M.
Abstract: A novel concept for an atmospheric solid oxide fuel cell (SOFC) hybrid system applying a sub‐atmospheric gas turbine is proposed. Based on a developed process model suitable operating conditions are studied. The resulting performance is compared to different state‐of‐the‐art SOFC system concepts. The comparison shows that pressurized SOFC/GT systems offer the highest electric efficiency. The novel concept as well as a two‐stage SOFC system offer lower efficiencies, but still well above 60%. However, avoiding the complex system requirements of pressurized SOFC/GT systems, these concepts are promising for highly efficient electricity generation.